MEME COMO ESTRATEGIA - Torres Quezada, Davis Alberto (Machala, 2020)
The present research work, has been carried out in the case study modality, has as a problem the use of memes as an educommunicative strategy and analyze the impact that the use of memes has within educational establishments. The meme has gained notoriety in social networks in the last decade, which can be used as a political or social satire or simply express something funny; In most cases the meme does not need a vast explanation, but it is explained by itself, perhaps that is why its popularity. Therefore, the general objective of the research is to determine the importance of the meme as an educommunicative strategy in the teaching and learning processes, through this, different stages were determined to develop the respective chapters, the problem arises when observing how the classes taught in the different educational establishments are maintained in a traditional way without giving way to the different educommunicative techniques that are there, at first glance but that sometimes are overlooked, for that reason with regard to the investigation the meme will be analyzed as a strategy educommunicative and the way in which it manages to be part of the activities in the classroom. Different techniques were carried out to give greater validity to the research work. First, a correct dismantling of information was proposed in which the different corresponding scientific articles were included, with this the theoretical framework was structured to have clear bases to continue with the remaining techniques, secondly, interviews were carried out with professionals who have done use of memes in educational establishments and the perception of these in the testimonies narrated by them was determined. Another of the techniques used was the survey directed at teachers, which allowed us to identify the perception that teachers have about this technique, finally, regarding the applied techniques, a bibliographic review was carried out, which allowed us to know the fundamental aspects of the meme in education and at the same time establish the main characteristics of educommunication strategies. Some of the results that the application of these techniques yielded is that most of the teachers know about the meme and when applying it in their classes they have witnessed that the meme has a high potential to be applied as an educommunicative strategy. Participation, dynamism, interest in learning, inclusion, are the fundamental aspects of the meme in education, but failing that, not all teachers are willing to use them as an educommunicative strategy. With regard to the conclusions of the work carried out, it was possible to identify and obtain an analysis on the perception of memes, thanks to the applied techniques that allowed obtaining favorable results for the research, although the opinion of the experts and the established surveys were a fundamental part of the development of the same, it is also intended to create a starting point for future researchers interested in wanting to address this issue of memes as an educommunicative strategy.
El presente trabajo de investigación, ha sido realizado en la modalidad de estudio de caso tiene como problemática la utilización de los memes como estrategia educomunicativa y analizar el impacto que tiene el uso de los memes dentro de los establecimientos educativos. El meme ha ganado notoriedad en las redes sociales, en la última década, mismo que puede ser utilizado como sátira política, social o simplemente expresa algo gracioso; en la mayoría de los casos el meme no necesita de una vasta explicación, sino que por sí mismo se explica, quizá a ello se deba su popularidad. Por lo tanto, el objetivo general de la investigación es determinar la importancia del meme como estrategia educomunicativa en los procesos de enseñanza y aprendizaje, mediante esto, se determinaron diferentes etapas para desarrollar los respectivos capítulos, la problemática surge al observar cómo las clases impartidas en los diferentes establecimientos educativos se mantienen de manera tradicional sin dar paso a las diferentes técnicas educomunicativas que están ahí, a simple vista pero que en ocasiones se nos pasan por alto, por ello en lo que respecta a la investigación se analizará al meme como una estrategia educomunicativa y la manera en cómo ésta logra formar parte de las actividades en el salón de clases. Se realizaron distintas técnicas para dar mayor validez al trabajo investigativo. Primero se planteó un correcto desmontaje de información en el cual se incluía los diferentes artículos científicos correspondientes, con ello se fue estructurando el marco teórico fundamentado para tener bases claras para seguir con las restantes técnicas, en segundo lugar se realizó entrevistas a profesionales que han hecho uso de los memes en establecimientos educativos y se determinó la percepción de estos en los testimonios narrados por ellos. Otra de las técnicas utilizadas fue la encuesta dirigida a los docentes la cual permitió identificar la percepción que tienen los docentes sobre esta técnica, por último en cuanto a las técnicas aplicadas se realizó la revisión bibliográfica la cual nos permitió saber los aspectos fundamentales del meme en la educación y a la vez establecer las principales características de las estrategias educomunicacionales. Algunos de los resultados que arrojó la aplicación de estas técnicas, es que la mayor parte de los docentes conocen sobre el meme y al aplicarlo en sus clases han sido testigos de que el meme tiene un alto potencial para ser aplicado como estrategia educomunicativa. La participación, dinamismo, interés por aprender, inclusión, son los aspectos fundamentales del meme en la educación, pero en su defecto no todos los docentes están dispuestos a utilizarlos como una estrategia educomunicativa. En lo que respecta a las conclusiones del trabajo realizado, se pudo identificar y obtener un análisis sobre la percepción de los memes, gracias a las técnicas aplicadas que permitieron obtener resultados favorables para la investigación, si bien la opinión de los expertos y las encuestas establecidas fueron parte fundamental del desarrollo de la misma, también se pretende crear un punto de partida para futuros investigadores interesados en querer abordar este tema de los memes como estrategia educomunicativa.
Keywords: EDUCOMUNICACION; DINAMISMO